The effect mentor and mentee interaction in problem solving and problem posing processes (Eurasian Journal of Philology Science and Education, 2016)
The classroom interaction between mentor (teacher) and mentee (candidate teacher) plays an important role in teaching and learning process in all parts of education at all grades. Problem solving and problem posing are also important elements in learning and teaching process. All problems that you encounter first and you don’t know how to solve them. The aim of the study here to explores and describes how mentor –mentee interaction develops the abilities of problem solving and problem posing. Research on the study with prospective mathematics and English teachers from Suleyman Demirel University is measured quantitively by using likert scale instrument. The results indicate that the regular and effective interactions with mentors and mentee give more positive significances in the problem solving and problem posing situations
Keywords: Mentoring; problem solving; problem posing.